2012
DOI: 10.1136/ejhpharm-2012-000074.149
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of an automated drug dispensing system in an intensive care unit

Abstract: Background In January 2011 the old Xeral-Calde hospital in the city of Lugo moved to new premises. The new hospital management decided to set up an automated storage and dispensing system in the intensive care unit. Purpose To analyse the automated Pyxis dispensing system in the hospital's intensive care unit (ICU) from the financial and human resources point of view. Materials and methods A drugs list was established for use in the Pyxis system. Large volume medicines and emergency trolley medicines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The use of barcode to identify drugs is another way to prevent medicines administration [4]. There are also several studies that have been realized in different hospitals to show the impact of using ADCs for reducing error rates as well as gaining time [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of barcode to identify drugs is another way to prevent medicines administration [4]. There are also several studies that have been realized in different hospitals to show the impact of using ADCs for reducing error rates as well as gaining time [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…They were able to notice the drastic reduction of the error rate. In another study (Serrano et al, 2012), the authors analyzed the impact of the automated dispensing system "Pyxis MedStation®" in the intensive care unit (ICU) both financially and in terms of human resources. By creating a list of drugs and using the management software 'Sinfohspharmacy', they showed that the monthly cost per patient with the Pyxis MedStation® system was reduced by 20.3%.…”
Section: Introductionmentioning
confidence: 99%